The Legitimacy of the International Integrated Reporting Council - Mădălina Dumitru; Raluca Gina Guşe (Journal of Accounting and Management Information Systems (JAMIS), 2017)
Our research is focused on the organizational legitimacy gained by the International Integrated Reporting Council (IIRC). We analyze all the answers received by IIRC in response to its Consultation Draft (CD) and match the responses with the legitimacy types, explaining the reasons of the users for participating in the standard-setting process. Also, for certain types of legitimacy, we analyze the information provided by the IIRC on its website. A qualitative approach is presented in this paper. We conclude that different groups of stakeholders grant different types of legitimacy. Our research contributes to the body of knowledge on integrated reporting in several ways. First, few studies discuss the legitimacy of a standard-setter, especially in the area of non-financial reporting. Second, our study considers the legitimacy granted by all the categories of stakeholders. Also, we identify the threats to the IIRC's legitimacy and provide guidance concerning sources of legitimacy that may be explored in the future.
Keywords: M41; M52; 650; Integrated reporting; legitimacy theory; International Integrated Reporting Council; International IR Framework; stakeholders; comment letters